OPTIMIZATION OF FLOATING TABLET CONTAINING ASPIRIN USING SIMPLEX LATTICE DESIGN - Siswanto, Agus (Indonesian Journal of Pharmacy, 2020)
Aspirin is an effective analgesic which is also used as an antiplatelet therapy for stroke prophylaxis. Aspirin in floating tablet formulations is used to improve the bioavailability. The aim of this study was to determine the optimum composition of floating tablets of aspirin by simplex lattice design (Design Expert 7.1.5). The tablets were prepared by direct compression technique, using polimers (Methocel K4M CR, Ethocel) and sodium bicarbonate (gas-generating agent) as independent variables. The optimum formula was determined based on numeric method with flow rate of tablet mass, floating lag time, C60, and Td as independent variables. The results indicated that the optimum composition of the matrix was Methocel K4M CR 16.94 %, NaHCO3 15.18 %, and Ethocel 17.88 %. It was observed that independent factors had significant contribution on all dependent variables.